Accelerated Thermal Ageing Effect On Insulating Paper Impregnated With Natural Ester Oil For Power Transformer - Muhammad Ridzuan., Nur Lidiya (2020)
Power transformer insulation systems consist of liquid and solid insulation. The liquid insulation is known as transformer oil, while the solid insulation is referred to as paper insulation and pressboard. In principle, materials used as transformer insulation are subjected to ageing process during the operation, which might lead to insulation failure. These ageing processes of transformer insulation are contributed either by temperature, time, moisture and oxygen. Recently, natural ester insulating oil (NEI) was proposed as an alternative to mineral oil (MO) due to the environmental, health and safety concerns from the public. Furthermore, MO filled transformers have a high tendency to cause fire aside from being non-biodegradable. Previous researchers have investigated the NEI properties by comparing with MO under thermal ageing. However, only a few of them conducted the thermal ageing with solid insulation but most of them do not include the effect of metal catalyst which can accelerate the ageing of the transformer. Moreover, most of the researcher compared only one type of NEI with MO in their studies. To overcome these shortcomings, accelerated ageing for two different types of NEI (i.e. palm and rapeseed) was conducted and MO is set as a reference. The first objective was to investigate the properties of oil tested under accelerated thermal ageing. The determination is done by measuring total acid number (TAN), AC breakdown voltage (BDV) and dissolved decay products (DDP). Next, a tensile strength (TS) measurement was conducted in order to identify the condition of kraft paper (KP) immersed in oil tested, and its correlation with oil properties. In order to verify the correlation, a spearman rank correlation was selected to measure the correlation coefficient. On the other hand, the compatibility of NEI with KP was determined by a regression model analysis to distinguish which types of NEI tested had the slowest degradation rate by predicting KP lifespan. The ageing setup was included KP and metal catalyst that was immersed in oils tested. The ageing sample was heated at temperature 130℃ inside the sealed oven for various durations (100, 250, 500, 1000 and 1500 hours). The properties of oils were tested after ageing to determine which oil give the best performance. It was found that the properties of oils tested became worsen as ageing period increased, which also affect the degradation of KP strength. The result shows that the strength of KP immersed in NEI was slowly degraded (palm 67.97%, rapeseed 54.36%) compared to KP immersed in MO (84.04%) at 1500 hours ageing. There was a negative correlation (> -0.8) observed between TS with TAN and TS with DDP for oils tested. While a very strong positive correlation was found between TS and BDV (>0.9) for oils tested. It was also noticed that rapeseed oil was well suited with KP under thermal ageing due to its slow degradation of tensile strength (54.36%). Moreover, the BDV of rapeseed oil maintains high (23 kV) at 1500 hours ageing compare to palm oil (20 kV). Therefore, it can be concluded that rapeseed oil was the most suitable to immersed KP in transformer compare to palm oil.